Abydos, Ägypten: Die Königsgräber der 1. und 2. Dynastie - Dreyer, Günter (e-Forschungsberichte des DAI, 2023)
The objective of the long-term project of re-examining the royal necropolis is to investigate the architectural development of the graves from the predynastic period to the end of the 2nd dynasty and to compile inventories of the funerary equipment. Fieldwork in 2011-13 focussed again on the huge tomb of king Djer. After revealing the northernmost rows of subsidiary burials, where several unknown chambers were discovered, the whole complex was backfilled. For comparative studies and to enhance the overall plan of the necropolis, smaller investigations were carried out at the hidden tumulus and the subsidiary chambers of king Wadj, some subsidiary chambers of queen Meret-Neith, and at the entrance of the burial chamber of king Adjib. Another objective was to check and repair the damages caused by recurrent looter’s activities since June 2011. In the dig house the study of small finds and pottery was continued.